Potensi Pemanfaatan Ulang Sampah Plastik Menjadi Eco-Paving Block - Haudi Hasaya; Reni Masrida; Dicky Firmansyah (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
Eco-paving block is a product used for construction consisting of sand and plastic mixes. In order to produce eco-paving blocks, the mixture of sand and concrete was substituted in part with sand and plastics. In order to properly mix plastics to create eco-paving blocks, a plastic smelter was used to generate heat and melt the plastic materials. The plastic material types used in this case was PETE or PETE, which has the characteristics of being flexible and high adhesive properties; along with ABS which can stand pressures. Based on the tests conducted with the plastic smelter using PET, ABS, and the combination of PET and ABS, the most promising result was shown with the combination of PET and ABS. This combination required 8 minutes 21 seconds for the plastics to become fully melted, and a temperature of 278oC. The combination of PET and ABS resulted in a mixture of plastics with strong adhesive properties and durability. This product could potentially be developed into eco-paving blocks. Additional studies regarding the optimum dosage combinations of PET and ABS plastics in eco-paving blocks can potentially be established in order to further optimize the usage of these plastics in eco-paving blocks.